The Supreme Court's Authority: Judicial Review of Statutes and By-Laws of Political Parties against Laws - Fahri Bachmid; Diani Indah Rachmitasari (LAW REFORM, 2022)
The debate about the authority of the Supreme Court to examine the  Statutes and bylaws of Political Parties against the Law has become a problem in the practice of law in Indonesia. This study aims to analyze the nature of the Supreme Court's authority to examine the Statutes and bylaws of political parties against the law. This research is a normative legal research. The data collection technique used in this research is literature study. The analytical technique used in this research is hermeneutic analysis method and interpretation. The results of this study indicate that political parties as public legal entities are present in all aspects of government and have an important contribution in determining the direction of constitutional development in Indonesia. Ratification of the Articles of association and by-laws of Political Parties based on a Ministerial Decree and announced in the State Gazette of the Republic of Indonesia. In this case, the Statutes and bylaws of a political party are statutory regulations under laws and Ministerial Decrees. The Supreme Court must carry out its supervisory function, including testing the Statutes and bylaws of political parties that are in conflict with the Law on Political Parties. This study concludes that the Supreme Court exercises broad powers as judge made law, especially in dealing with complex cases, such as the Statutes and bylaws issues of political parties.